CXXC5 is required for cardiac looping relating to TGFβ signaling pathway in zebrafish. (1st July 2016) - Peng, Xiyang; Li, Guanming; Wang, Yuequn; Zhuang, Jian; Luo, Rong; Chen, Jimei; Chen, Fa; Shi, Yan; Li, Jiani; Zhou, Zuoqiong; Mo, Xiaoyang; Liu, Xianchu; et al.
Abstract: Background: CXXC-type zinc-finger protein CXXC5 has been reported to be associated with the development of cardiovascular disease. Recently, through signaling pathway screening we found that CXXC5 activated Tgfβ and myocardial differentiation signaling pathways simultaneously. Although the physiological and pathological function of CXXC5 in many organs has been well elucidated, its function in heart remains unclear. Methods and results: Here, we found that zebrafish CXXC5 and SMAD were interacting through ZF-CXXC and MH1 domain. Over-expression of CXXC5 in cardiomyocyte increased the luciferase report activity of Tgfβ signaling pathway. Spatiotemporal expression profile of cxxc5 showed that it consistently expressed during cardiogenesis. Knockdown of cxxc5 in zebrafish displayed looping defects, cardiac dysplasia, pericardial edema, and decreased contraction ability, accompanied with down-regulation of members referring to cardiac looping downstream genes of Tgfβ signaling pathway, such as nkx2.5, hand2, and has2 . Co-injection of hand2 mRNA with cxxc5 morpholino rescued the cardiac looping detects. Conclusion: Our study is the first to provide an in vivo evidence for cxxc5 regulating heart development and cardiac looping via Tgfβ related signaling pathway. This finding suggested that CXXC5 may serve as a possible marker that has potential diagnostic and prognostic value in fetus with congenital heart disease.